Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Long-term exposure to fine particulate matter and its constituents, genetic susceptibility, and incident bipolar disorder - Xinru Zhao; Yudiyang Ma; Ning Chen; Lei Zheng; Meiqi Xing; Feipeng Cui; Jianing Wang; Linxi Tang; Yaohua Tian; Peng Xiong; Yu Chen (Environmental Pollution, 2026)

Ejecta from Chaffee S Crater in Chang’E-6 Landing Site Constrained by Seifertite-Bearing Norite - Zhan Zhou; Sen Hu; Yubing Gao; Linxi Li; Huicun He; Liang Gao; Mengfan Qiu; Lixin Gu; Xu Tang; Xiaoguang Li; Wei Yang; Yangting Lin; et al. (Journal of Earth Science, 2026)

Effects of Dietary Supplementation with Selenium-Enriched Lactobacillus plantarum on Growth, Hepatic Antioxidant Capacity, and Intestinal Microbiota of Largemouth Bass (Micropterus salmoides) - Chengxu Ruan; Junhao Tang; Xiufang Liu; Junwei Chen; Linxi Cheng; Xucong Lv (Fishes, 2026)
This study compared the effects of dietary Lactobacillus plantarum (Lpl) and selenium-enriched L. plantarum (Lpl_se) on the growth, hepatic antioxidant capacity, and intestinal microbiota of juvenile largemouth bass (initial weight 12.50 ± 0.81 g). Following a 58-day trial in an indoor rearing system, data were analyzed using one-way ANOVA followed by Tukey’s HSD test. Results showed that both Lpl and Lpl_se significantly improved growth versus the control (Weight Gain Rate: 379.82% and 387.18% vs. 326.56%; p

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Sustainable electronics manufacturing using environmentally safe short chain fluorinated Gemini surfactants for high efficiency printed circuit board cleaning - Yunye Huang; Lewen Huang; Chen Zhou; Danni Tang; Xiangyu Yin; Longqiang Xiao; Rui Zhao; Linxi Hou (Journal of Cleaner Production, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Associations between residential greenness exposure during pregnancy and bone mineral density in early childhood - Yibing Zhu; Linxi Tang; Yudiyang Ma; Bin Sun; Haibo Li; Feipeng Cui; Jingmin Guo; Yaohua Tian; Chong Miao (Environmental Research, 2025)

Crystallinity-driven charge dynamics in π-stacked COF enables robust PET-RAFT polymerization under aerobic conditions - Danni Tang; Xin Cao; Zhen Lu; Longqiang Xiao; Linxi Hou (Chemical Engineering Journal, 2025)

Prenatal exposure to ozone and bone mineral density in early childhood: Susceptible window identification - Linxi Tang; Yibing Zhu; Yudiyang Ma; Chong Miao; Bin Sun; Feipeng Cui; Jingmin Guo; Yaohua Tian (Environmental Research, 2025)

Discovery of carbonaceous chondritic fragment in Chang'e-5 regolith samples - Linxi Li; Hejiu Hui; Sen Hu; Qiuli Li; Yi Chen; Wei Yang; Guoqiang Tang; Lihui Jia; Xiaoguang Li; Lixin Gu; Fuyuan Wu (Icarus, 2025)

Bioavailability and ecological risk assessment of metal pollutants in ambient PM2.5 in Beijing - Yunzhe Li; Yanyi Qin; Lisha Zhang; Linxi Qi; Shuifeng Wang; Jinghua Guo; Aohan Tang; Keith Goulding; Xuejun Liu (Science of The Total Environment, 2024)

Association of residential greenness with incident pneumonia: A prospective cohort study - Lei Zheng; Jianing Wang; Linxi Tang; Yudiyang Ma; Yaohua Tian (Science of The Total Environment, 2024)

Long-term exposure to reduced specific-size ambient particulate matter and progression of arterial stiffness among Chinese adults - Dankang Li; Shouling Wu; Linxi Tang; Shuohua Chen; Feipeng Cui; Yudiyang Ma; Run Liu; Jianing Wang; Yaohua Tian (Journal of Hazardous Materials, 2024)

Residential greenness and incident idiopathic pulmonary fibrosis: A prospective study - Linxi Tang; Feipeng Cui; Yudiyang Ma; Dankang Li; Jianing Wang; Run Liu; Yaohua Tian (Environmental Research, 2024)

The adverse impact of maternal ozone exposure on fetal growth in utero and the interaction with residential greenness - Yibing Zhu; Yudiyang Ma; Linxi Tang; Haibo Li; Chong Miao; Hua Cao; Yaohua Tian (Journal of Hazardous Materials, 2024)

Bisphenol a alternatives suppress human and rat aromatase activity: QSAR structure-activity relationship and in silico docking analysis - Miaomiao Xia; Jingyi Zheng; Sailin Chen; Yunbing Tang; Shaowei Wang; Zhongyao Ji; Ting Hao; Huitao Li; Linxi Li; Ren-shan Ge; Yi Liu (Food and Chemical Toxicology, 2024)

The association of residential greenness, genetic susceptibility and telomere length: A cross-sectional study - Linxi Tang; Dankang Li; Yudiyang Ma; Jianing Wang; Yaohua Tian (Landscape and Urban Planning, 2023)

Enhanced Antimony Removal by Yeast Powder Modified with KMnO4 - Linxi Tang; Chunhua Zhang; Jinyan Peng; Ying Ge (Water, Air, & Soil Pollution, 2023)

Optimizing root architecture and increasing transporter gene expression are strategies to promote selenium uptake by high-se accumulating rice cultivar - Mu Zhang; Lolita Wilson; Guofang Xing; Linxi Jiang; Shuanhu Tang (Plant and Soil, 2020)

SUMOylation of Fragile X Mental Retardation Protein: A Critical Mechanism of FMRP-Mediated Neuronal Function - Mingzhu Tang; Liqun Lu; Feng Xie; Linxi Chen (Neuroscience Bulletin, 2018)